The extension of wealth gap in education: the impact of economic inequality perception on students' value perception - Ziyan Li (Environment and Social Psychology, 2025)
Abstract: Wealth gap is one of the key issues facing modern society. The inequality in social distribution and the risk of class solidification caused by it have gradually penetrated into the field of education. For young students, the economic inequality perception brought about by wealth gap affects students' correct values. Therefore, the study proposes hypotheses H1 and H2 to analyze the specific impact of economic inequality perception on students’ educational value perceptions and fairness beliefs. The study conducts a questionnaire survey on 463 middle school students, and conducts regression analysis and mediation analysis based on the survey results. A negative correlation was observed between students' economic inequality perception and their educational value perception, at -0.24, (p<0.01). Students' economic inequality perception and their equal opportunity perception also showed a significant negative correlation, at -0.27 (p<0.01). Economic inequality perception also had negative impacts on educational values (β=-0.17, t=4.14 and p<0.001), while fairness perception and the equal opportunity perception had a significant mediating effect.